Dharma and ‘Custom’: Semantic Persistence, Semantic Change and the Anxieties of the Principled Few - Bowles, Adam (Religions of South Asia, 2016)
This article does three things. First, it argues that the usage of dharma in the sense of ’customary practice’, which is found in compounds such as desadharma and kuladharma, can be traced back to the Atharvaveda. Second, it argues that in the Dharmasastra tradition this usage of the word dharma as ’custom’ ought to be distinguished from acara, which is also often taken in the sense of ’custom’, because acara frequently implies a hieratic sense of ’customary behaviour’, especially in its association with the cultured practices of particular elites (the sat, sadhu, or sista). Therefore, dharma in the usage this article is concerned with is a broader term for ’custom’ than acara. And, third, it suggests that when the Dharmasastra writers restricted the currency of such customary dharmas to cases where existing sacred texts (sruti or smrti) could not be called upon, they were reaffirming that such dharmas were worldly rather than transcendent, and not to be confused with the transcendent dharma the principled few now identified with these sacred texts–a development attributable to other changes that shifted the word dharma to the very centre of brahmanic ideology.